Madame Bovary : provincial manners - Flaubert, Gustave, 1821-1880 (Oxford world's classics (Oxford University Press), 2004)
Emma Bovary yearns for a life of luxury and passion of the kind she reads about in romantic novels. But life with her country doctor husband in the provinces is unutterably boring, and she embarks on love affairs to realize her fantasies. This new translation by Margaret Mauldon perfectly captures Flaubert's distinctive style. - ;'Would this misery go on forever? Was there no escape? And yet she was every bit as good as all those other women who led happy lives!'. When Emma Rouault marries Charles Bovary she imagines she will pass into the life of luxury and passion that she reads about in sen.